Work smart, not hard: analysis of delays faced by clinical trials investigating spinal fusion using Protocol AI - Katia Schiegg; Philipp Khlebnikov; Florian Meer; Joel Kühl; Poorya Amini; Janine Antonov; Emin Aghayev; Emin Aghayev; Stephan Radzanowski; Quentin Haas (Frontiers in Surgery)
IntroductionDegenerative diseases of the spine are increasingly prevalent with age. Spinal fusion is a common treatment if non-invasive or less-invasive treatment approaches have not been successful. Numerous clinical trials on spinal fusion are started every year to investigate novel technologies worldwide. However, a substiantial amount of trials are terminated prior to completion.Research questionIn this study, we analyzed the historical performance of all clinical trials on spinal fusion since 2010.Material and methodsThe identification of related trials was carried out using Protocol AI, which is the Risklick's software. It collects and updates clinical trial data from various sources, including clinical trial registries and datasets from the World Health Organization. Protocol AI has automatically extracted the data on trial, categorized them, and clustered them in trial phases.ResultsThe historical probability of early termination for a clinical trial investigating spinal fusion was approximately 25%. The average trial delay for completed trials was 10.6 months. With an average anticipated trial duration approaching 40 months, the observed delay represents an extension of 25% of the anticipated trial duration for completed trials. Trials facing delay and failure predominantly reported critical issues with patient recruitment.Dicsussion and conclusionThis study emphasizes the importance of implementing a strict risk management plan and recruitment plans, while suggesting professionals to implement standardized enrollment monitoring analyzes during the course of the trial. The amelioration of recruitment policies could substantially maximize the performance of trials within the field, benefiting patients and all stakeholders involved.